INNOVATIVE WASTEWATER TREATMENT AS A PREREQUISITE FOR THE USE OF SLUDGE IN AGRICULTURE - Piuković Babičković, Blaženka; Vojinović, Željko; Vukadinović, Predrag (Economics of Agriculture, 2018)
This paper is based on the research done in water supply companies on the territory of Vojvodina in the Republic of Serbia. The paper presents an innovative model for wastewater treatment, because wastewater treatment and the disposal of sludge, produced during such treatment, are issues to be tackled not only by the Republic of Serbia, but also other countries in the region and elsewhere. The aim of the paper is to point out, how correct wastewater and sludge treatment can produce sludge, which has valuable agronomic properties. The paper seeks to encourage the correct use of sludge in agriculture in line with Directive 86/278/EEC, adopted by the Council of the European Economic Community to promote the use of sludge in agriculture on reasonable grounds, by ensuring its proper use.